(untitled) (Praxis Educativa, 2021)
This paper shares some interpretations of stories of young people linked to the decision-making process that they are going through regarding the fact of having to live outside the family environment, decision justified mainly in the pursuit of continuing studies at a higher level, a topic developed in a research called “Student migration and the beginning of a university career. Youth experiences: from the imagined project to the concrete project”. We worked from a longitudinal qualitative approach, identifying aspects of the youngster’s trajectory, from the sixth grade of secondary school to the first two years of arrival in the city of Córdoba. In this instance, we will focus on the step prior to migration. Interviews were conducted with young people and mothers, in 2018 and 2019, in order to know how the mobility and study project is imagined and defined, as well as options, expectations and decisions.